Polycyclic aromatic hydrocarbon exposure effects on trajectories of maternal and adolescent mental health - Mariah DeSerisy; Leilani Salas; Emiliya Akhundova; Dahiana Pena; Jacob W. Cohen; David Pagliaccio; Julie Herbstman; Virginia Rauh; Amy E. Margolis (BMC, 2024)
Abstract Background Parental psychological distress is a well-known risk factor for developmental psychopathology, with longer term parental distress associated with worse youth mental health. Neurotoxicant exposure during pregnancy is a risk factor for both poor maternal and youth mental health. The impact of one class of pollutant, polycyclic aromatic hydrocarbons (PAH), on long-term trajectories of maternal distress and youth self-reported mental health symptoms in adolescence has been understudied. Methods PAH exposure was measured by DNA adducts in maternal blood sampled during the third trimester of pregnancy. Maternal distress, operationalized as maternal demoralization, was measured at 11 timepoints (prenatal to child age 16). Adolescent mental health symptoms were measured at age 13-15. Follow up analyses examined a subset of measures available at age 15-20 years. Structural equation modeling examined associations between PAH exposure during pregnancy and latent growth metrics of maternal distress, and between maternal distress (intercept and slope) and youth mental health symptoms in a prospective longitudinal birth cohort (N = 564 dyads). Results Higher prenatal PAH exposure was associated with higher concurrent maternal distress. Prenatal maternal distress was associated with adolescent's self-reported anxiety, depression, and externalizing problems. On average, maternal distress declined over time; a slower decline in mother's distress across the course of the child's life was associated with greater self-reported anxiety and externalizing problems in youth. Conclusions Our findings are consistent with an intergenerational framework of environmental effects on mental health: PAH exposure during pregnancy affects maternal mental health, which in turn influences mental health outcomes for youth well into adolescence. Future research is necessary to elucidate the possible social and biological mechanisms (e.g., parenting, epigenetics) underlying the intergenerational transmission of the negative effects of pollution on mental health in caregiver-child dyads.